North America - Russell, John, fl. 1733-1795. (C. Dilly and G.G. and J. Robinson, 1799)
Hand-colored print. Roman numerals are used to number the 15 United States. The area west of the Mississippi River is largely blank except for rivers and other waterways. This map was formerly classified as 33 MAP-0-81